2020
DOI: 10.1111/rec.13169
|View full text |Cite
|
Sign up to set email alerts
|

Soil seed bank in different vegetation types in the Loess Plateau region and its role in vegetation restoration

Abstract: In the Loess Plateau region, soil erosion is a serious problem. Vegetation restoration is an effective approach to control soil erosion and improve ecosystems. The soil seed bank generally plays an important role in vegetation restoration after disturbance. Thus, we reviewed soil seed bank studies to reveal the soil seed bank characteristics and its role in vegetation restoration in three vegetation types (forest, forest-steppe, and steppe). We selected 38 seed bank studies and analyzed several seed bank chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 55 publications
2
7
0
3
Order By: Relevance
“…Overall, the percentage of germinated seeds represented by tree species in the seed banks was low (only 5.7%) and was much lower than the percentage represented by herbs and shrubs. In addition to representing only a small percentage of the total seed bank density, tree species represented only a small percentage of the total seed bank species richness, a finding that is consistent with previous reports for forest soil seed banks [52,53]. This result might be explained by the small number of large seeds typically produced by trees species and by the large number of small seeds typically produced by shrubs and herbs [54].…”
Section: Discussionsupporting
confidence: 89%
“…Overall, the percentage of germinated seeds represented by tree species in the seed banks was low (only 5.7%) and was much lower than the percentage represented by herbs and shrubs. In addition to representing only a small percentage of the total seed bank density, tree species represented only a small percentage of the total seed bank species richness, a finding that is consistent with previous reports for forest soil seed banks [52,53]. This result might be explained by the small number of large seeds typically produced by trees species and by the large number of small seeds typically produced by shrubs and herbs [54].…”
Section: Discussionsupporting
confidence: 89%
“…The loess hilly region is one of the most critical soil erosion areas in China, which constrains the ecological and sustainable development of agriculture [1,2]. Ecological vegetation restoration is an effective method for controlling soil erosion, a strenuous task that needs to be executed over long time periods in the loess hilly region [3,4]. Soil water and heat are important factors that influence vegetation development, characterized using soil moisture and temperature [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly because vegetation transports SOC and various organic carbon fractions to the soil through soil surface plant and animal residues, microbial content, and plant root exudates (Wang et al, 2020a). Studies have shown that during long-term vegetation restoration, differences in the selection of restored tree species have led to differences in the recovery of their aboveground components (biodiversity, richness) (Engel and Abella, 2011), resulting in large differences in surface plant community structure (Fu et al, 2020;Wang et al, 2020b). However, vegetation types with a more complex surface composition can provide a higher litter, cover area, and thickness, which are conducive to the accumulation of labile carbon pools in the soil (Wang et al, 2021).…”
Section: Differences In Soil Carbon Pools Between Vegetation Restorat...mentioning
confidence: 99%